SEBUAH PENDEKATAN ONTOLOGIS DALAM MEMAHAMI FILSAFAT SIVA SIDDHANTA - I Gusti Made Widya Sena (Sanjiwani: Jurnal Filsafat, 2018)
Hindu religion as one of the religions that has complexity of philosophy in the development of his doctrines using the basis of religious knowledge, direct views and conclusions as a process of philosophical thinking. Siva Siddhanta is the core or conclusion of the Siva doctrines that describes various concepts in it such as cosmology, metaphysics, theology, philosophy until the concept of unity with God. The ontological perspective of Siva Siddhanta philosophical system derived from the essence of Siva as the ultimate reality. This is final doctrine and conclusion from Siva is known as Siva Siddhanta. Siva Siddhanta is a essence of Vedanta. Siva is the ultimate reality, it is eternal, without being, free, one, without beginning and end, without cause. Siva pervades the whole world with his Sakti, she uses Sakti as the energy of consciousness of Siva, which is actually the body Siva